Legal Study of the Role of the Honorary Board of Election Administrators in Realizing Democratic Elections - Agustien Cherly Wereh,; Athur N. Tuwaidan,; Yoan Barbara Runtunuwu,; Fatimah Hs,; Ngismatul K, (Technium Social Sciences Journal, 2024)
The primary goal of this research is to evaluate the role of the Honorary Council for the Implementation of Elections in prosecuting election organizers who break the code of ethics, as well as to understand how the DKPP imposes sanctions on election organizer members who breach the code of ethics. This study employed normative legal research. The author's study reveals that where Article 1 paragraph (24) indicates, "The Election Organizer Honor Council, hereinafter abbreviated as DKPP, is an entity in charge of dealing with infractions of the Election Organizer's code of ethics. The provisions that mention the sanctions for violations of the election organizer's code of ethics are regulated in DKPP Regulation No. 1 of 2021 concerning the Second Amendment to the regulation of the Election Organizer Honorary Council No. 3 of 2017 concerning Procedural Guidelines for the Code of Ethics for General Election Organizers Article 31 paragraph 4 indicates that if the DKPP's finalization judges that the Respondent and/or Reported Party breached, the DKPP imposes sanctions in the form of a written warning, temporary dismissal, or permanent dismissal. Thus, it is determined that the implementation of the code of ethics in Indonesia, particularly in the election management body, DKPP, must prevent violations of the code of ethics committed by election organizers in order to ensure democratic elections.